PENGARUH PENDINGIN AIR DAN ES TERHADAP HASIL PIROLISIS MINAK PLASTIK - Bakhtiar Permana Putra; Wawan Trisnadi Putra; Fadelan Fadelan; Sudarno Sudarno; Yoyok Winardi (Universitas Muhammadiyah Ponorogo, 2022)
Plastic waste is a trend that continues to increase along with economic growth and an increase in population. Millions of tons of plastic are produced annually from low to large scale. One way to reduce plastic waste is to use the pyrolysis process. Condenser performance is influenced by several things, including condenser design. The condenser design used in this pyrolysis device is a water and ice-cooled condenser with a spiral type. The results of the pyrolysis process are then analyzed by observing the experiment directly then concluding and determining the results of the experiments that have been carried out in the form of tables and graphs to obtain comparisons. What was observed in this experiment was the effect of water and ice cooling media on the amount of plastic oil produced. Pyrolysis experiments with ice cube coolers get more plastic oil results. For the first experiment using 1000 gr PP plastic using plain water cooler, in a combustion time of 180 minutes and a reactor temperature of 2500ºC, we get 130 ml of plastic oil. The second experiment used 1000 gr PP plastic with ordinary water as a coolant mixed with ice cubes in a burning time of 180 minutes and a reactor temperature of 250ºC to get 340 ml of plastic oil. The third experiment used 1000 gr PP plastic with ice cubes as a cooler for 180 minutes of combustion and a reactor temperature of 250ºC to get 600 ml of plastic oil.